Rapid Screening and Structural Characterization of Antioxidants from the Extract of Selaginella doederleinii Hieron with DPPH-UPLC-Q-TOF/MS Method. (22nd February 2015) - Wang, Gang; Yao, Shun; Zhang, Xiu-Xiu; Song, Hang
Abstract : 2, 2-Diphenyl-1-picrylhydrazyl-ultra-high performance liquid chromatography-Q-time-of-flight mass spectrometry (DPPH-UPLC-Q-TOF/MS), as a rapid and efficient means, now was used for the first time to screen antioxidants from Selaginella doederleinii . The nine biflavone compounds were screened as potential antioxidants. The biflavones were structurally identified and divided into the three types, that is, amentoflavone-type, robustaflavone-type, and hinokiflavone-type biflavonoids. Among the compounds bilobetin (3) and putraflavone (8) were found from Selaginella doederleinii for the first time and others including amentoflavone (1), robustaflavone (2), 4′-methoxy robustaflavone (4), podocarpusflavone A (5), hinokiflavone (6), ginkgetin (7), and heveaflavone (9) were identified previously in the plant. Moreover, nine biflavones possessed a good antioxidant activity via their DPPH free radical scavenging. It demonstrates that DPPH-UPLC-Q-TOF/MS exhibits strong capacity in separation and identification for small molecule. The method is suitable for rapid screening of antioxidants without the need for complicated systems and additional instruments.